The Application Of Coaching İn The Preparation Of Employees For Work Performance - Marta Matulcikova; Daniela Brevenikova (European Scientific Journal, ESJ, 2016)
The aim of the present paper based on theoretical and empirical analysis is the description and evaluation of benefits of coaching in education in organizations in the Slovak Republic. Our intention is to work out the issue of coaching from the aspect of individual coaching, group coaching and team coaching, as well as from the perspective of understanding the role of coaching as part of leading. The present paper contains partial results of the research conducted under the first stage of work on the research project KEGA 014EU-4/2016 – ‟Preparation of the content and structure of courses focused on the development of basic business knowledge and skills of graduates from non-economic health service fields of study”. Results presented in the paper relate to the application of coaching in institutions employing respondents of the research and to types and kinds of coaching. The research was conducted by means of the interview method and the questionnaire method. The data collection was held in two stages (each containing several rounds) in order to obtain respondents’ responses of high information value.